HUBUNGAN TRANSFORMATIONAL LEADERSHIP DENGAN INNOVATIVE WORK BEHAVIOR PADA KARYAWAN MILENIAL - Thalia, Hesti Juni; Harsanti, Intaglia (LPPM Institut Pendidikan Nusantara Global, 2023)
In the current era of digitalization, it is crucial for employees to be innovative. To achieve innovative work behavior in employees, the support of a leader is essential. Transformational leadership is believed to be one of the main driving factors for employees to be innovative. This research aims to examine the positive relationship between transformational leadership and innovative work behavior among millennial employees. The study utilized the innovative work behavior scale adapted from Janssen (2000) and the Multifactor Leadership Questionnaire (MLQ). A quantitative method was employed in this study, with a sample of 142 employees selected through purposive sampling technique. Data analysis involved using Pearson's product-moment correlation to test the hypotheses. Based on the research findings, a correlation coefficient of r = 0.600 with a significance value of 0.000 (p < 0.01) was obtained, indicating a highly significant positive relationship between transformational leadership and innovative work behavior among millennial employees. The higher the level of transformational leadership, the higher the level of innovative work behavior. Conversely, lower transformational leadership corresponds to lower innovative work behavior among millennial employees.